The Port City of Haiphong, 1874–1940: The Position of the Chinese Community in a French Colonial City - Nguyen Thi Hoai Phuong (Universitas Gadjah Mada, 2021)
This article discusses the position of the Chinese community in Haiphong, the largest port city in Northern Vietnam during the French colonial period. The Chinese had arrived and lived in Haiphong, as well as many other places in Vietnam long before the advent of the French. Nevertheless, a large-scale influx of Chinese migrants to Haiphong only happened after the French established colonial rule over Indochina and took full control of the town in the late nineteenth century. Haiphong became a strategic port in the transportation system of French Indochina, as well as within the French colonial empire. In Haiphong, the Chinese gathered in a separate residential quarter having the social and cultural life distinct from the French and Vietnamese communities. Yet, they were actively engaged in various economic activities of the town, notetably trade, intrustry, and financial services. The bombardment and occupation of Haiphong by the Japanese army in late 1940 caused great damages and casualties to the Chinese community. The prolonged warfares and the establishment of the communist regime in Vietnam after 1945 virtually ended the economic hegemony of the Chinese in Haiphong, as well other cities in Northern Vietnam.